Republic of Estonia : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides the details of the IMF's projections and estimates on Estonia's basic data; gross domestic product by expenditure, origin, and income approach; real gross domestic product by origin; employment by sector; balance of payments; foreign direct investment inflows and outflows by countries; foreign direct investment outflows and inflows by sectors during 1996-2000; maturity and currency composition of deposits and loans; general government revenue and expenditure during 1996-2001; gross external debt; foreign assets; net external debt during 1997-2000, and so on.